2012
DOI: 10.1002/psc.2408
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of leptin responsiveness in diet‐induced obese mice using an optimized leptin analog in combination with exendin‐4 or FGF21

Abstract: The identification of leptin as a mediator of body weight regulation provided much initial excitement for the treatment of obesity. Unfortunately, leptin monotherapy is insufficient in reversing obesity in rodents or humans. Recent findings suggest that amylin is able to restore leptin sensitivity and when used in combination with leptin enhances body weight loss in obese rodents and humans. However, as the uniqueness of this combination therapy remains unclear, we assessed whether co-administration of leptin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
117
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(125 citation statements)
references
References 54 publications
(66 reference statements)
6
117
0
2
Order By: Relevance
“…Studies in animals also showed that pre-treatment of diet-induced obese animals with amylin restored leptin's ability to phosphorylate Stat3 in the hypothalamus, suggesting that this gut peptide might reduce the activity of neural circuits that cause leptin resistance (Turek et al 2010). In animals, leptin's efficacy has also been augmented in combinations with other peptides or hormones raising the possibility that in time it could emerge as part of a combination therapy for obesity (Muller et al 2012). Bariatric surgery is an alternative means for inducing weight loss and, while invasive, can be extremely effective.…”
Section: Leptin Resistancementioning
confidence: 99%
“…Studies in animals also showed that pre-treatment of diet-induced obese animals with amylin restored leptin's ability to phosphorylate Stat3 in the hypothalamus, suggesting that this gut peptide might reduce the activity of neural circuits that cause leptin resistance (Turek et al 2010). In animals, leptin's efficacy has also been augmented in combinations with other peptides or hormones raising the possibility that in time it could emerge as part of a combination therapy for obesity (Muller et al 2012). Bariatric surgery is an alternative means for inducing weight loss and, while invasive, can be extremely effective.…”
Section: Leptin Resistancementioning
confidence: 99%
“…Compared with hLeptin (t 1/2 = 0.6 h), the hLeptin-Herceptin fusion protein has an extended t 1/2 of 11.8 h (SI Appendix, Table S2). The Fc-hLeptin fusion and PEGylated hLeptin were shown to have half-lives of 10 h in mice and 48 h in rat, respectively (41)(42)(43). Compared with the hGH-CDR3H-coil-Herceptin fusion, hLeptin-CDR3H-coil-Herceptin displays a reduced half-life, which is attributable in part to the different species used in the two PK studies, and may also be due to proteolytic degradation of the fusion protein in vivo (44).…”
Section: Resultsmentioning
confidence: 99%
“…87 Leptin combined with GLP-1 analogs did produce the stronger effects on eating and body weight than single compounds, but the interaction seemed to be (mathematically) additive rather than synergistic. 88 Further, and in contrast to the amylin-induced sensitization of animals to leptin, the effect was only present in animals that had already lost a substantial amount of weight or after animals were switched from an obesogenic high-fat diet to regular rodent chow; 89 hence, manipulations which themselves may affect the leptin sensitivity.…”
Section: Interactions Of Amylin With Other Factors Involved In the Comentioning
confidence: 98%